A enzima histidinol desidrogenase de mycobacterium tuberculosis como alvo para o desenvolvimento de drogas : caracterização bioquímica - Nunes, José Eduardo Sacconi (2011)
In 2009, tuberculosis (TB) was responsible for 1.3 million deaths worldwide. The incidence rates reached 9.4 millions and the World Health Organization (WHO) estimative indicates that one third of the world population is infected by Mycobacterium tuberculosis, the main agent responsible for the disease. The lack of new drugs released on market, the long period treatment presenting side effects (causing the abandon by the patients) and the cases with HIV co-infection contributed to the appearance of multi drug resistant strains (MDR-TB) and extensively drug resistant strains (XDR-TB). It's clear, thus, that the development of new drugs to fight TB is necessary and fundamental to the success in eradicating this disease. The histidine biosynthesis pathway emerge in this context offering attractive targets, given that its present in prokaryotes, lower eukaryotes and plants, but absent in animals. The last enzyme in the route is called Histidinol Dehydrogenase and is responsible for the conversion of L-Histidinol into LHistidine. Its essentiality to the bacilli was confirmed by gene knockout, confirming its potential for the development of inhibitory compounds. In this work, a purification protocol was developed, producing the enzyme in the homogeneous form in quantities sufficient to carry its biochemical characterization. The enzyme needs a divalent metal ion in the active site to catalyze the reaction. The kinetic constants were determined, as well as the mechanism, the pH rate profiles and the interaction of its substrates and products by isothermal titration calorimetry. A tridimensional model for its structure was constructed by sequence homology, allowing the analysis of the interaction of the substrates and metal in the active site. The results obtained will allow the rational design of molecules that act as inhibitors.